A Limnological study on (Bany-Hassan) Stream/Karbala-Iraq - Sura F. Hassan; Fikrat M. Hassan (Al-Qadisiyah Journal of Pure Science, 2017)
The present study conducted on Bany-Hassan stream within the holy Karbala governorate due to its importance as sources of agricultural area and domestic uses throughout the study area. The study included measurement of physical and chemical properties of the stream, moreover chlorophyll-a for the period study between December 2012 to June 2013. Five sites were selected along the stream. The mean ranges of the studied properties were recorded: 4-38C° for Air temperature, 9.5-25.4 C° water temperature, 983-1440 μS/cm for Electric conductivity, 0.613-0.869 ‰ for salinity, 122-137 mg/l for total alkalinity, 0.28-81mg/l for total dissolved solid ranged. The present results revealed that the stream was oxygenated and the dissolved oxygen ranged 7-12.8 mg/l. Nutrient concentrations were ranged 96.52-212.64 mg/l Sulfate, 0.48-5 mg/l silicate, 0.019-1 mg/l total nitrogen and 0.018- 0.68 mg/l total phosphorus. Chlorophyll-a ranged 0.04-15.56 μg/l. Total organic carbon, electric conductivity and pH for sediments were ranged 0.12-2.14%, 510-3853μS/cm and 6.7-7.6 respectively. The results indicated that the study area was not matching the international standards and also for Iraqi standards for drinking.